The Effect of Certification on Teacher Performance and Learning Outcomes of Madrasah Students - Suharmoko, Suharmoko; Yudiawan, Agus (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
The purpose of this study was to determine: (1) the performance of certified teachers; (2) student learning outcomes; (3) the effect of teacher certification on teacher performance; and (4) the effect of teacher certification on student learning outcomes in MTs. Model Sorong City. The research approach used is quantitative with survey techniques. The method of determining the sample used is a saturated sample. That is, 20 respondents sample the entire population. The analytical method used is a simple linear regression method. The results of this study indicate that: (1) the performance of certified teachers is good (3.56); (2) student learning outcomes are classified as good (3.97); (3) there is a positive and significant effect of teacher certification on teacher performance by 73.3%; and (4) there is a positive and significant effect of teacher certification on student learning outcomes by 64.3%. It can be concluded that the provision of certification allowances can improve teacher performance and student learning outcomes in MTs. Model Sorong City.